(3OjhGf GHf GdeYJRs - (3CHh GdYHGS, GHf GdeYJR, YHO Gddg Hf eMeO GdeYJR HGddgs
(3ChdgG (B:s
(3HSe Gddg bGd Ydi bGajI GdCda (B: (3hSGQjI dG Jed GdHcG LQi OeYgG aj NOhO GdKQi (B** (3SQJ JbOM GdUHM aj djdgG jHQb cgfOjI JfJVi (B** (3adeG QfJ LdLdJ aj GdSeG HQYO CLT cLQ GdQMG s
(3BNQgG (B:s
(3hbGd CjVG aj GdRgO (B: (3CdG jG faS Cf JQVj HahJ aCfJ YRjRI CHOG YfjI (B** (3OYj Yfc GdeWGeY hGdCeGfj ace CefjI LdHJ efjI JeJ bGajI GdjGA aj GdRgO hHJeGegG Je GdcJGHs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3EHQGgje HGTG RGO CSYO (B( (3ZjQ eDQN (B) - (3YHO GdHGbj (B( (3ZjQ eDQN (B) - (3ZjQ hGVM GdGSe eDQN H TgQ TYHGf SfI (B1251 (3g`s
Keywords: (3GdCOHs